Nevoid basal cell carcinoma syndrome: an analysis of four familial and two sporadic cases - Pinto, Lucielma Salmito Soares; Carlos-Bregni, Román; Martelli Júnior, Hercílio; Melo Filho, Mário Rodrigues; Wilson Delgado Azañero; León, Jorge Esquiche; Lopes, Márcio Ajudarte; Almeida, Oslei Paes; Jorge, Jacks (Journal of Oral Diagnosis, 2016)
The nevoid basal cell carcinoma syndrome (NBCCS) is an autosomal dominant disorder with complete penetrance and variable expressivity. It is caused by mutations in the patched gene, mapped to chromosome 9q22.3-q31. Its characteristics include multiple basal cell carcinomas, odontogenic keratocysts, vertebral and rib anomalies, and intracranial calcifications. Here, we describe the features of 4 familial and 2 sporadic cases of the NBCCS.